2023
DOI: 10.1038/s41598-023-38340-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the p53 pathway in polycystic ovarian syndrome pathogenesis and apoptosis enhancement in human granulosa cells through transcriptome data analysis

M. Zanjirband,
R. Hodayi,
Z. Safaeinejad
et al.

Abstract: The polycystic ovarian syndrome (PCOS) is closely associated with enhanced apoptosis of granulosa cells, which have a vital role in maturation of oocytes. p53 plays a critical role in the regulation of apoptosis and cell cycle arrest, metabolism and insulin resistance. The aim of this study was to investigate the impact of p53 pathway in enhancing apoptosis and abnormal function of granulosa cells. In this study, microarray analysis and RNA sequencing were downloaded from the GEO and used as datasets. Principa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…The p53 gene family member (TP53 in humans) is a guardian of the female germline and plays a key role in determining the oocyte fate upon damage [ 34 ]. P53 is involved in many cellular processes, including steroid hormone regulation, and its role in the pathogenesis of polycystic ovarian syndrome (PCOS)—a complex endocrinologic disorder with increasing risk of infertility, ovulatory disfunction, hyperandrogenism and raised LH:FSH ratio [ 35 ]—has been proposed. Recent investigations of increased rates of embryonic implantation failure and miscarriage in women with polymorphisms in the p53 gene could demonstrate the importance of p53 in female fertility and IVF success [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The p53 gene family member (TP53 in humans) is a guardian of the female germline and plays a key role in determining the oocyte fate upon damage [ 34 ]. P53 is involved in many cellular processes, including steroid hormone regulation, and its role in the pathogenesis of polycystic ovarian syndrome (PCOS)—a complex endocrinologic disorder with increasing risk of infertility, ovulatory disfunction, hyperandrogenism and raised LH:FSH ratio [ 35 ]—has been proposed. Recent investigations of increased rates of embryonic implantation failure and miscarriage in women with polymorphisms in the p53 gene could demonstrate the importance of p53 in female fertility and IVF success [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main suppressor of p53, that is, MDM2, also showed downregulation, leading to a decrease in the ubiquitin-dependent degradation of p53, and, consequently an increase in its cellular expression and transcriptional activity. 70 The T A B L E 2 Association of PDCD4 expression with cell cycle progression, proliferation, and apoptosis.…”
Section: Role Of Pdcd4 In Cell Cycle Proliferation and Apoptosismentioning
confidence: 99%
“…These preantral follicles showed a higher survival capacity [2,3], with granulosa cells (GCs) responding prematurely to the luteinizing hormone (LH) [4] and exhibiting a higher proliferation rate than normal [5]. However, when examining follicles at a later stage of development, such as preovulatory follicles obtained from women undergoing in vitro fertilization (IVF) protocols, several studies reported a significant increase in the apoptosis capacity of GCs in PCOS [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%